Performance of Compost Filtration Practice for Green Infrastructure Stormwater Applications. (1st September 2013) - Faucette, Britt; Cardoso, Fatima; Mulbry, Walter; Millner, Pat
ABSTRACT: : Urban storm water runoff poses a substantial threat of pollution to receiving surface waters. Green infrastructure, low impact development, green building ordinances, National Pollutant Discharge Elimination System (NPDES) storm water permit compliance, and Total Maximum Daily Load (TMDL) implementation strategies have become national priorities; however, designers need more sustainable, low‐cost solutions to meet these goals and guidelines. The objective of this study was to determine the multiple‐event removal efficiency and capacity of compost filter socks (FS) and filter socks with natural sorbents (NS) to remove soluble phosphorus, ammonium‐nitrogen, nitrate‐nitrogen, E. coli, Enterococcus, and oil from urban storm water runoff. Treatments were exposed to simulated storm water pollutant concentrations consistent with urban runoff originating from impervious surfaces, such as parking lots and roadways. Treatments were exposed to a maximum of 25 runoff events, or when removal efficiencies were ≤ 25%, whichever occurred first. Experiments were conducted in triplicate. The filter socks with natural sorbents removed significantly greater soluble phosphorus than the filter socks alone, removing a total of 237 mg/linear m over eight runoff events, or an average of 34%. The filter socks with natural sorbents removed 54% of ammonium‐nitrogen over 25 runoff events, or 533 mg/linear m, and only 11% of nitrate‐nitrogen, or 228 mg/linear m. The filter socks and filter socks with natural sorbents both removed 99% of oil over 25 runoff events, or a total load of 38, 486 mg/linear m. Over 25 runoff events the filter socks with natural sorbents removed E. coli and Enteroccocus at 85% and 65%, or a total load of 3.14 CFUs x 10 8 /linear m and 1.5 CFUs x 10 9 /linear m, respectively; both were significantly greater than treatment by filter socks alone. Based on these experiments, this technique can be used to reduce soluble pollutants from storm water over multiple runoff events.